2007
DOI: 10.1111/j.1399-5618.2007.00454.x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal cellular energy and phospholipid metabolism in the left dorsolateral prefrontal cortex of medication‐free individuals with bipolar disorder: an in vivo1H MRS study

Abstract: These findings provide further evidence that the pathophysiology of BD involves impairment in the DLPFC. Our findings can be interpreted as evidence for reduced cellular energy and phospholipid metabolism, consistent with the hypothesis of mitochondrial dysfunction in BD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0
12

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(71 citation statements)
references
References 61 publications
(82 reference statements)
4
55
0
12
Order By: Relevance
“…After correcting for osmolarity, the level of mI returned to its original value (Haussinger et al 1994). An increase of mI was also found at bipolar disorder (Frey et al 2005(Frey et al , 2007.…”
Section: Myo-inositolmentioning
confidence: 62%
“…After correcting for osmolarity, the level of mI returned to its original value (Haussinger et al 1994). An increase of mI was also found at bipolar disorder (Frey et al 2005(Frey et al , 2007.…”
Section: Myo-inositolmentioning
confidence: 62%
“…Decreased levels of expression of subunits of the mitochondrial electron transport chain have been reported for both patients with BD and schizophrenia. 4 Since cell loss and morphological alterations are found in the PFC in patients with BD and schizophrenia, [50][51][52][53][54] cellular dysfunction produced by protein oxidation may contribute to these alterations. This may lead to a decline in the proper functioning of the PFC.…”
Section: Discussionmentioning
confidence: 99%
“…NAA reduction has been detected in different cerebral regions such as hippocampus (Bertolino et al 2003 ;Deicken et al 2003 ), basal ganglia (Frye et al 2007a ;Port et al 2008 ), occipital cortex (Bhagwagar et al 2007 ), frontal lobe (Cecil et al 2002 ), orbitofrontal cortex (Cecil et al 2002 ), and DLPFC Winsberg et al 2000 ;Sassi et al 2005 ), including younger medicated bipolar patients (Chang et al 2003 ). On the contrary, other studies reported preserved NAA concentrations in BD in DLPFC (Bertolino et al 2003 ;Brambilla et al 2005 ;Frey et al 2005Frey et al , 2007Ongür et al 2008 ), hippocampus (Colla et al 2009 ;Senaratne et al 2009 ), basal ganglia (Kato et al 1996 ;Ohara et al 1998 ;Hamakawa et al 1998 ;Bertolino et al 2003 ;Malhi et al 2007 ), frontal and temporal lobes (Castillo et al 2000 ;Cecil et al 2002 ;Bertolino et al 2003 ;Port et al 2008 ), thalamus (Port et al 2008 ), insula , and ACC (Davanzo et al 2001(Davanzo et al , 2003Bertolino et al 2003 ;Dager et al 2004 ;Frye et al 2007a ;Ongür et al 2008 ;Patel et al 2008 ;Port et al 2008 ;Brady et al 2012 ). Finally, when compared to healthy controls, increased NAA levels were also shown in basal ganglia …”
Section: Naa (N-acetyl-aspartate)mentioning
confidence: 95%
“…Indeed, most of the negative studies included small samples of medicated patients (less than 20 patients) (Davanzo et al 2001 ;Frey et al 2007a , b ;Kaufman et al 2009 ;Singh et al 2010 ), whereas 8/14 studies that found increased glutamatergic levels had larger populations (>20), also composed by medication-free patients. Finally, since creatine has usually been used as an internal reference, it cannot be excluded that changes in creatine levels might infl uence glutamate concentration when reported as a ratio to creatine itself Frey et al 2007 ).…”
Section: Glutamatergic Neurotoxicitymentioning
confidence: 99%